Alkaloids from Fissistigma latifolium (Dunal) Merr - Alias, A.; Hazni, H.; Jaafar, F.M.; Awang, K.; Ismail, N.H. (MDPI AG, 2010)
A phytochemical study of the bark of Fissistigma latifolium (Annonaceae) yielded a new aporphine alkaloid, (-)-N-methylguattescidine (1), and eight known alkaloids: liriodenine (2), oxoxylopine (3), (-)-asimilobine (4), dimethyltryptamine (5), (-)-remerine (6), (-)-anonaine (7), columbamine (8) and lysicamine (9). The compounds were isolated using various chromatographic methods and structural elucidation was accomplished by means of spectroscopic methods, notably 1D-NMR ((1)H, (13)C, DEPT), 2D-NMR (COSY, HMQC, HMBC), UV, IR and MS.